A QUALITATIVE APPROACH OF EVALUATING HEALTH AND SAFETY PROGRAM (CASE STUDY: PT HUTAMA KARYA MANADO - Sulu, Reynald .; Pandowo, Merinda . (Universitas Sam Ratulangi, 2018)
Abstract: Humans or employees play a very important role in the production process activity in the company, in addition to the machinery and raw materials. So human beings as employees need to feel safe and guaranteed while they work, it’s not only concerns the prevention of loss of these employees but also to maintain the attitude of cooperation and work ability of these employees. This study aims to analyze the implementation of health and safety program at PT. Hutama Karya Branch Manado. This research utilizes descriptive qualitative method Populations and samples in this study are the leaders and employees of PT Hutama Karya Branch Manado, using snowball technique in collecting sample research from informants. The results of this research describe the occupational safety and health programs implemented by company, that consist of preventive programs and curative programs for occupational health while the providing of self-protection tools, toolbox meeting routine and instruction board for occupational safety. This study concludes that the company’s occupational safety and health program have a more positive impact and recommends that the company should improve and update the programs and facilities.Keywords: occupational health, occupational safety, occupational health and safety